Metformin was associated with lower all-cause mortality in type 2 diabetes with acute coronary syndrome: A Nationwide registry with propensity score-matched analysis. (15th September 2019) - Jong, Chien-Boon; Chen, Kuan-Yu; Hsieh, Mu-Yang; Su, Fang-Ying; Wu, Chih-Cheng; Voon, Wen-Chol; Hsieh, I-Chang; Shyu, Kou-Gi; Chong, Jun-Ted; Lin, Wei-Shiang; Hsu, Chih-Neng; Ueng, Kwo-Chang; et al.
Abstract: Background: No randomized controlled trials evaluating metformin therapy efficacy in patients with type 2 diabetes mellitus (DM) and acute coronary syndrome (ACS) have been reported. We aimed to examine the mortality benefit of metformin therapy in patients with type 2 DM and ACS, compared with non-metformin anti-diabetes agents users. Methods: Data were extracted from the prospective nationwide ACS-DM Taiwan Society of Cardiology registry. Propensity score (PS) matching on baseline characteristics and treatment measures was performed for metformin versus non-metformin users. The Cox proportional hazards model was used to compare mortality outcomes among the PS-matched cohort as the primary analysis. The Cox proportional hazards models adjusting for all pre-determined covariates and quintiles of the PS among the overall population were performed as the secondary analyses. Results: Of 1157 patients with type 2 DM and ACS receiving anti-diabetes agents, 78 patients (6.7%) died over the 2-year follow-up period. After PS matching, 318 metformin users were matched with 318 non-metformin users. Metformin users had a lower all-cause mortality rate (adjusted hazard ratio [aHR] 0.50, 95% confidence interval [CI] 0.26–0.95) in the primary analysis. The survival benefit of metformin therapy was consistent in the secondary analyses (aHR 0.30, 95% CI 0.17–0.54 while adjusting for all pre-determined covariates, and aHR 0.34, 95% CI 0.19–0.59 while adjusting for quintiles of the PS). Conclusions: Among patients with type 2 DM and ACS, metformin was associated with lower all-cause mortality. However, a detrimental effect of any of the comparators could not be excluded. Highlights: Metformin was associated with lower mortality in T2DM with ACS, in modern PCI era. Similar benefit was found in patients with CKD, LV dysfunction and contrast exposure. Similar benefit was found in patients with old age and advanced DM severity.